TAZKIYAT AL-NAFS DENGAN TAHFIZH AL-QUR’AN SANTRI PONDOK PESANTREN AL-BAROKAH KOTA MALANG - Roisatul, Ani; Mohammad Asrori; Muhammad In’am Esha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Al-Barokah Islamic Boarding School Malang is a boarding school that provides a tahfizh Al-Qur'an program. The students do not only focus on memorizing the Al-Qur'an, but are also involved in various religious activities that help support the purification of their souls. This study aims to determine tazkiyat al-nafs with tahfizh Al-Qur'an of students at Al-Barokah Islamic Boarding School in Malang City. Meanwhile, the approach in this study is a qualitative method, while data collection techniques use interviews, observations, and documentation. Data analysis techniques carry out data reduction, data presentation, and drawing conclusions. Checking the validity of the data uses source triangulation, theory triangulation, and technique triangulation. The results of this study indicate that: 1) The learning strategy of tazkiyat al-nafs in the context of students' memorization of the Al-Qur'an is as follows: Al-Qur'an memorization program, Al-Qur'an tahsin program, qiro'ah sab'ah, learning the book of Jalalain interpretation and studying the yellow book, b) Internalization of tazkiyat al-nafs with students' memorization of the Al-Qur'an, namely: Zikir, taqwiyyatul hifdzi prayer, obligatory prayer in congregation, tahajud prayer and dhuha prayer, tahlil, istighosah, routine diba'an and yasin, and tasmi' akbar, c) The results of learning tazkiyat al-nafs in students' memorization of the Al-Qur'an such as: Helping individuals who are patient, humble, and responsible, the boarding school environment can form manners, increase academic achievement through the tahfizh program, and the habit of worship can increase enthusiasm and peace of mind.